The relationship between hypomagnesemia and ICU mortality in severe hemorrhagic stroke patients: an observational multicentre study on eICU database - Xinzhao Jiang; Faliang Gao; Zongjie Shi; Fang Liu; Wenyan Zhao; Guihong Gong (BMC Cardiovascular Disorders)
Abstract Background Hemorrhagic stroke is a potentially fatal condition with high mortality and morbidity. However, there is a lack of evidence for this relationship in critically ill patients with hemorrhagic stroke. This study aims to explore the relationship between hypomagnesemia and ICU mortality in severe hemorrhagic stroke patients. Methods The study included 2,026 severe hemorrhagic stroke patients from the Electronic Intensive Care Unit Collaborative Study database, categorized into hypomagnesemia and non-hypomagnesemia groups based on serum magnesium levels. Primary outcome was ICU mortality. Secondary outcome was mechanical ventilation use. Multivariate Cox proportional hazards regression analyses were used to study the relationship between hypomagnesemia and the outcomes. We also performed a cumulative survival rate analysis by Kaplan–Meier curves. Results A total of 2,026 severe hemorrhagic stroke patients, aged over 16 and hospitalized in the ICU for more than 24 h, were enrolled. Among them, 277 (13.7%) died in the ICU, and hypomagnesemia was observed in 489 patients. Multivariable Cox regression analyses demonstrated that hypomagnesemia was related to a 28% increased risk of ICU mortality (HR 1.28, 95% CI [1.02–1.68], p = 0.035) and a 15% increased risk of mechanical ventilation use (HR 1.15, 95% CI [1.04—1.33], p = 0.010) in severe hemorrhagic stroke patients. Conclusions Our findings suggested that hypomagnesemia is associated with increased risks of ICU mortality and mechanical ventilation use in severe hemorrhagic stroke patients. Future randomized, prospective studies are needed to elucidate the role of hypomagnesemia and explore potential interventions.